Diagnostic performances of Schistosoma haematobium and Schistosoma mansoni recombinant proteins, peptides and chimeric proteins antibody based tests. Systematic scoping review - Arthur Vengesai; Victor Muleya; Herald Midzi; Tryphine Vimbai Tinago; Isaac Chipako; Marble Manuwa; Thajasvarie Naicker; Takafira Mduluza (Public Library of Science, 2023)
Background